Case Report: Limbic encephalitis following treatment with durvalumab for small-cell lung cancer - Moss, Thomas T.; Stavem, Knut; Aandahl, Astrid; Gløersen, Anne S.; Grønberg, Bjørn H.; Neumann, Kirill; Vedeler, Christian A.; Lundqvist, Christofer (Frontiers in Immunology, 2023)
Background: Durvalumab is an immune checkpoint Inhibitor (ICIs) that is used in the treatment of malignant tumors, such as lung cancer and melanoma. ICIs are associated with immune-related adverse events including autoimmune encephalitis, although both paraneoplastic phenomena and ICI treatment may lead to autoimmunity.We describe a 72-year old male patient with small-cell lung cancer, who during adjuvant treatment with Durvalumab developed GABABR1 and GAD65 antibodies and both diabetes and autoimmune limbic encephalitis. Because he was followed prospectively as part of a treatment study, we had access to repeated serum samples and cognitive assessments over time prior to developing encephalitis and diabetes, in addition to later assessments. A high titer of GABABR1 antibodies appeared early, while GAD65 antibodies appeared later with a lower titer in parallel with the development of diabetes. As he subsequently developed clinical signs of encephalitis, verified by EEG and brain MRI, he also had CSF GABABR1 antibodies. Durvalumab was discontinued and steroid treatment with subsequent plasmapheresis were started, resulting in reduction of both CSF and serum antibody levels.Clinical signs of encephalitis gradually improved.This case illustrates the importance of being aware of possible serious autoimmune adverse reactions, including neurological syndromes such as encephalitis, when treating patients with high risk of para-neoplasia with ICIs. In addition, the case shows the development of autoantibodies over time.